Intermittent Hypoxia Influences Alveolar Bone Proper Microstructure via Hypoxia-Inducible Factor and VEGF Expression in Periodontal Ligaments of Growing Rats - Oishi, Shuji; Shimizu, Yasuhiro; Hosomichi, Jun; Kuma, Yoichiro; Maeda, Hideyuki; Nagai, Hisashi; Usumi-Fujita, Risa; Kaneko, Sawa; Shibutani, Naoki; Suzuki, Jun-ichi; Yoshida, Ken-ichi; Ono, Takashi (Frontiers in Physiology, 2016)
Intermittent hypoxia (IH) recapitulates morphological changes in the maxillofacial bones in children with obstructive sleep apnea (OSA). Recently, we found that IH increased bone mineral density (BMD) in the inter-radicular alveolar bone (reflecting enhanced osteogenesis) in the mandibular first molar (M1) region in the growing rats, but the underlying mechanism remains unknown. In this study, we focused on the hypoxia-inducible factor (HIF) pathway to assess the effect of IH by testing the null hypothesis of no significant differences in the mRNA-expression levels of relevant factors associated with the HIF pathway, between control rats and growing rats with IH. To test the null hypothesis, we investigated how IH enhances mandibular osteogenesis in the alveolar bone proper with respect to HIF-1α and vascular endothelial growth factor (VEGF) in periodontal ligament (PDL) tissues. Seven-week-old male Sprague–Dawley rats were exposed to IH for 3 weeks. The microstructure and BMD in the alveolar bone proper of the distal root of the mandibular M1 were evaluated using micro-computed tomography (micro-CT). Expression of HIF-1α and VEGF mRNA in PDL tissues were measured, whereas osteogenesis was evaluated by measuring mRNA levels for alkaline phosphatase (ALP) and bone morphogenetic protein-2 (BMP-2). The null hypothesis was rejected: we found an increase in the expression of all of these markers after IH exposure. The results provided the first indication that IH enhanced osteogenesis of the mandibular M1 region in association with PDL angiogenesis during growth via HIF-1α in an animal model.